Syncope caused by lymphomatous encasement of the internal carotid artery. Issue 12 (30th December 2021) - Altshuler, Ellery; Aryan, Mahmoud; Delaune, Jess; Lynch, James
Abstract : We present a case of a 77-year-old man who reported 5 months of syncopal episodes. He was found to have diffuse large B-cell lymphoma encasing the left internal carotid artery but not impeding blood flow. The syncopal episodes resolved after his first cycle of chemotherapy. Recurrent syncope in non-cardiac lymphomas and other head and neck masses is exceedingly rare and may be due to reflex syncope prompted by carotid baroreceptor activation. There are 11 previously described cases of recurrent syncope associated with non-cardiac lymphoma. In all cases, lymphadenopathy abutting the carotid artery was present and the syncopal episodes resolved with treatment. Our case illustrates that malignancy should be considered in patients with unexplained recurrent syncope.